Peptidomics profiling and biological activities of grape pomace protein hydrolysates - Knuf, Franziska (2025)
Grape pomace protein isolate was hydrolysed by Alcalase, Flavourzyme and Protease either individually or in combination to produce hydrolysates with antihypertensive and antimicrobial properties. The degree of hydrolysis (DH) ranged between 22 and 52 % for Protease and Flavourzyme, respectively. Among all treatments, hydrolysates prepared using Flavourzyme exhibited the highest angiotensin-converting enzyme inhibitory (ACEi) activity, with an IC50 value of 91 μg/mL. The peptidomics analysis revealed that the peptides identified in Flavourzyme hydrolysate presented molecular features compatible with its bioactivity, like a high density ofACEi sequences per peptide. The hydrolysates were also able to inhibit the growth of Escherichia coli in a range between 9 and 54 % for Alcalase and Alcalase + Flavourzyme, respectively. Peptides in the most active hydrolysate evidenced a high occurrence of proline residues, which is a structural feature of some antimicrobial peptides.